2021
DOI: 10.3390/microorganisms9102108
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Artificial Fusarium Infection on Oat Grain Quality

Abstract: Adverse environmental conditions, such as various biotic and abiotic stresses, are the primary reason for decreased crop productivity. Oat, as one of the world’s major crops, is an important cereal in human nutrition. The aim of this work was to analyze the effect of inoculation with two species of the genus Fusarium on the selected qualitative parameters of oat grain intended for the food industry. Artificial inoculation caused a statistically significant decrease in the content of starch, oleic, linoleic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This is in good accordance with literature as it has been reported that F. culmorum inoculation reduces the overall lipid content in cereals due to the predominant reduction of oleic acid. 46 F. graminearum infection had a minor inuence on the correlation loading plot. Also, it has been described that its infection reduces the lipid content but to a lesser extent than for F. culmorum infection.…”
Section: Discussionmentioning
confidence: 92%
“…This is in good accordance with literature as it has been reported that F. culmorum inoculation reduces the overall lipid content in cereals due to the predominant reduction of oleic acid. 46 F. graminearum infection had a minor inuence on the correlation loading plot. Also, it has been described that its infection reduces the lipid content but to a lesser extent than for F. culmorum infection.…”
Section: Discussionmentioning
confidence: 92%
“…These metabolites were near Rujana and Foxyl on the PCA bi-plot and could potentially affect their resistance to Fusarium spp. In support of that is the fact that heptadecanoic acid (C 17: 0, margarinic or margaric acid) is a saturated fatty acid and that 9-(Z)-hexadecenoic (C 16: 1, palmitoleic acid) is one of the main unsaturated fatty acids of wheat [ 41 , 42 ], where previous research reported that approximately 40 identified metabolites associated with fatty acid metabolic pathways may potentially affect cereal resistance against F. graminearum [ 43 ]. Furthermore, these metabolites from fatty acid metabolic pathways could have role in basal immunity and gene-mediated resistance in plants [ 44 ], but could also be involved in the breaking down of products such as oxylipins [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the scientific interest in the Fusarium diseases of oat arose due to increased demand for a high-quality grain of this crop, which is used both in the feed and food industries. Fusarium rot of cereals, including oat, causes significant economic loss, as well as various human and animal diseases [ 25 ]. In this regard, there is a need for safe and effective approaches to controlling the spread of Fusarium rot.…”
Section: Introductionmentioning
confidence: 99%